Model Matematika Penyebaran Penyakit Leptospirosis Pada Populasi Manusia Dan Hewan - Delvika Gusdiani; Media Rosha (Journal of Mathematics UNP, 2020)
Abstract — Leptospirosis is an infectious disease that can affect humans and animals. This infectious disease is an animal disease that can infect humans. This disease is a public health problem around the world, especially Indonesia which has high rainfall. Individuals most at risk of developing leptospirosis are farmers who work in rice fields, plantation workers, slaughterhouse workers and veterinarians, laboratory workers and veterinarians. The purpose of this study was to form a mathematical model of the spread of leptospirosis in human and animal populations. This research is a basic research using theoretical methods, namely analyzing relevant theories with the problem of the spread of leptospirosis in human and animal populations based on existing literature studies. Based on the analysis results obtained two fixed points, namely a fixed point free from the spread of leptospirosis and an endemic fixed point for the spread of leptospirosis. The stability of this model is stable at both fixed points of leptospirosis in human and animal populations. The high rate of leptospirosis in the population will cause leptospirosis to become epidemic in the population.Keywords — Mathematical Model, Infectious Diseases, Leptospirosis.